2019
DOI: 10.2147/ijn.s215835
|View full text |Cite
|
Sign up to set email alerts
|

<p>Formulation And Evaluation Of Nanostructured Lipid Carriers (NLCs) Of 20(S)-Protopanaxadiol (PPD) By Box-Behnken Design</p>

Abstract: Background20(S)-Protopanaxadiol (PPD) has a higher anti-wrinkle effect than the other glycone forms of ginsenosides. However, as PPD has low solubility in water and a high molecular weight, it cannot easily penetrate the stratum corneum layer, which is the rate-limiting step of topical skin delivery. Thus, the objective was to enhance the topical skin deposition of PPD using an optimized nanostructured lipid carriers (NLC) formulation. NLC formulations were optimized using a Box-Behnken design.Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Notably, the mean particle size of the NLCs formulations (F2, 498 nm; F4, 246 nm) containing Capmul MCM EP as an oil was larger than that of the SLNs formulations (F1, 165 nm; F3, 133 nm). This increase in particle size is consistent with other previous studies that have reported larger sizes in NLCs formulations when oil is added into the solid lipid phase of SLNs [ 30 , 31 , 32 ]. However, the high EE (>95%) and orobol content (≈1.0%) in the F1–F4 formulations were not significantly affected by the existence of oil and an increase of particle size.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the mean particle size of the NLCs formulations (F2, 498 nm; F4, 246 nm) containing Capmul MCM EP as an oil was larger than that of the SLNs formulations (F1, 165 nm; F3, 133 nm). This increase in particle size is consistent with other previous studies that have reported larger sizes in NLCs formulations when oil is added into the solid lipid phase of SLNs [ 30 , 31 , 32 ]. However, the high EE (>95%) and orobol content (≈1.0%) in the F1–F4 formulations were not significantly affected by the existence of oil and an increase of particle size.…”
Section: Discussionsupporting
confidence: 92%
“…For these reasons, many researchers are searching for new phytochemicals with use as topical formulations to increase their stability and delivery efficiency. [30][31][32][33][34] In this study, for the first time, we found a metabolite of genistein, orobol, which has anti-atopic effects in animals and cell models.…”
Section: Discussionmentioning
confidence: 89%
“…The dependent variables selected were mean particles size (Y 1 ), zeta potential (Y 2 ) and encapsulation efficiency (Y 3 ). The lower (−1), medium (0) and higher (+1) values for each factor were selected on the basis of literature survey [ 12 , 24 , 25 ]. The data analysis was performed by ANOVA.…”
Section: Methodsmentioning
confidence: 99%